Directions for the Development of Private Entrepreneurship and Further Improvement of the Business Environment (Eurasian Research Bulletin, 2022)
Private entrepreneurship is carried out in a certain area: on the scale of the country, region, city or village. A certain working environment must be in place for private businesses to be effective. Such an environment is embodied on the scale of some regions, embodying the implementation of business functions. In general, the environment of private entrepreneurship is mainly implemented as a result of the interdependence of the following four factors: legal, political, social and economic factors. They can also be formed in the form of positive or encouraging. In the article, a scientific conclusion, proposal and practical recommendations were given on the directions of improving the systems of improving the business environment in the Republic of Uzbekistan